Measuring Cultural Diversity Impact in Hospitality Industry Leadership: Managerial Communication Perspective from Five Star Hotels in Kathmandu Valley, Nepal - Paudel, Udaya Raj; Puri, Sudip; Parajuli, Seeprata; Devkota, Niranjan; Bhandari, Udbodh (Journal of Tourism & Adventure, 2021)
This study aims to measure the cultural diversity impacts in hospitality industry leadership from the perspective of managerial communication. Data were obtained from all the 10 five star hotels in Kathmandu valley. 167 respondents were sampled from the managers of five star hotels in Kathmandu valley, Nepal using structured questionnaire. Data analysis is made using descriptive analysis and Leadership Practices Index measured through dimension suggested by GLOBE Model. The study found out that maximum majority (48.48%) employees were the residents of Bagmati Province itself. For effective functioning of any organization workplace communication plays crucial role. Though numerous challenges are faced by employees working in hospitality industries in terms of communication 96% of respondents believed that managerial communication problem could be overcome if better tactics were used. Upon responding the importance of communication in workplace 54.76% employees stated that effective communication would help managers to set goals and targets for attaining objective of the hotel or their department followed by its importance at the time of serving guests and working in team while coordinating. Likewise, 41.07% feels that effective communication makes employees feel secure and helps to achieve targets. Also, 40.48% feel easy to work in team with the help of effective communication. 19.05% thinks through effective communication exchanging necessary ideas become easier. Communication leadership scale suggested by GLOBE model shows the maximum number of leaders are performance oriented i.e., 83.03% whereas assertiveness, Power Distance and in-group collectivism are the least but still above the 50%, which shows the leader still maintain power distance, least in-group collectivism. Hence, based on the findings of the study, the study concluded that managerial communication skills impact in hospitality business for its growth and maximization. This original study is crucial for hotels, government agencies and prospective employees of hospitality sector of Nepal and worldwide at large.